Can primaquine therapy for vivax malaria be improved? - Baird, J; Rieckmann, K (2003)
The incidence and range of endemic malaria caused by Plasmodium vivax has expanded during the past 30 years. This parasite forms hypnozoites in the liver, creating a persistent reservoir of infection. Primaquine (PQ), introduced 50 years ago, is the only drug available to eliminate hypnozoites. However, lengthy treatment courses and follow-up periods are not conducive to assessing the effectiveness of this drug in preventing relapses. Resistance to standard therapy could be widespread. Studies are urgently needed to gauge this problem and to determine the safety, tolerability and efficacy of shorter courses and higher doses of PQ.